Progesterone, Lipoic Acid, and Sulforaphane as Promising Antioxidants for Retinal Diseases: A Review - Vicente Hernández-Rabaza; Rosa López-Pedrajas; Inmaculada Almansa (Antioxidants, 2019)
Oxidative stress has been documented to be a key factor in the cause and progression of different retinal diseases. Oxidative cellular unbalance triggers a sequence of reactions which prompt cell degeneration and retinal dysfunction, both hallmarks of several retinal pathologies. There is no effective treatment, yet, for many retinal diseases. Antioxidant treatment have been pointed out to be an encouraging palliative treatment; the beneficial effects documented involve slowing the progression of the disease, a reduction of cell degeneration, and improvement of retinal functions. There is a vast information corpus on antioxidant candidates. In this review, we expose three of the main antioxidant treatments, selected for their promising results that has been reported to date. Recently, the sulforaphane, an isothiocyanate molecule, has been unveiled as a neuroprotective candidate, by its antioxidant properties. Progesterone, a neurosteroid has been proposed to be a solid and effective neuroprotective agent. Finally, the lipoic acid, an organosulfur compound, is a well-recognized antioxidant. All of them, have been tested and studied on different retinal disease models. In this review, we summarized the published results of these works, to offer a general view of the current antioxidant treatment advances, including the main effects and mechanisms described.